The InSight-HP3 mole on Mars: Lessons learned from attempts to penetrate to depth in the Martian soil. Issue 8 (15th April 2022) - Spohn, Tilman; Hudson, Troy L.; Witte, Lars; Wippermann, Torben; Wisniewski, Lukasz; Kedziora, Bartosz; Vrettos, Christos; Lorenz, Ralph D.; Golombek, Matthew; Lichtenheldt, Roy; Grott, Matthias; Knollenberg, Jörg; et al.
Highlights: The NASA InSight Mars mission payload includes a surface heat flow probe. A small penetrator implements a string of temperature sensors in the soil. The penetrator is equipped with sensors to measure the thermal conductivity. Unfortunately, the penetrator did not reach the required depth. Lessons learned for future attempts to penetrate in the Martian soil are discussed. Abstract: The NASA InSight lander mission to Mars payload includes the Heat Flow and Physical Properties Package HP 3 to measure the surface heat flow. The package was designed to use a small penetrator - nicknamed the mole - to implement a vertical string of temperature sensors in the soil to a depth of 5 m. The mole itself is equipped with sensors to measure a thermal conductivity-depth profile as it proceeds to depth. The heat flow is calculated from the product of the temperature gradient and the thermal conductivity. To avoid the perturbation caused by annual surface temperature variations, the measurements need to be taken at a depth between 3 m and 5 m. The mole is designed to penetrate cohesionless soil similar in rheology to quartz sand which is expected to provide a good analogue material for Martian sand. The sand would provide friction to the buried mole hull to balance the remaining recoil of the mole hammer mechanism that drives the mole forward. Unfortunately, the mole did not penetrate more than 40 cm, roughly a mole length. The failure to penetrate deeper is largely due to a cohesive duricrust of a few tens of centimeter thickness that failed to provide the required friction. Although a suppressor mass and spring as part of the mole hammer mechanism absorb much of the recoil, the available mass did not allow designing a system that fully eliminated the recoil. The mole penetrated to 40 cm depth benefiting from friction provided by springs in the support structure from which it was deployed and from friction and direct support provided by the InSight Instrument Deployment Arm. In addition, the Martian soil provided unexpected levels of penetration resistance that would have motivated designing a more powerful mole. The low weight of the mole support structure was not sufficient to guide the mole penetrating vertically. Roughly doubling the overall mass of the instrument package would have allowed to design a more robust system with little or no recoil, more energy of the mole hammer mechanism and a more massive support structure. In addition, to cope with duricrust a mechanism to support the mole to a depth of about two mole lengths should be considered.